The Epidemiology of Chronic Critical Illness in the United States - Kahn, Jeremy M. (Crit Care Med, 2015)
OBJECTIVE: The epidemiology of chronic critical illness is not well characterized. We sought to determine the incidence, outcomes and associated costs of chronic critical illness in the United States. DESIGN: Population-based cohort study using data from the United States Healthcare Costs and Utilization Project from 2004 to 2009. SETTING: Acute care hospitals in Massachusetts, North Carolina, Nebraska, New York and Washington. PATIENTS: Adult and pediatric patients meeting a consensus-derived definition for chronic critical illness, which included one of 6 eligible clinical conditions (prolonged acute mechanical ventilation, tracheotomy, stroke, traumatic brain injury, sepsis or severe wounds) plus at least 8 days in an intensive care unit. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Out of 3,235,741 admissions to an intensive care unit during the study period, 246,151 (7.6%) met the consensus definition for chronic critical illness. The most common eligibility conditions were prolonged acute mechanical ventilation (72.0% of eligible admissions) and sepsis (63.7% of eligible admissions). Among patients meeting chronic critical illness criteria through sepsis, the infections were community-acquired in 48.5% and hospital acquired in 51.5%. In-hospital mortality was 30.9% with little change over the study period. The overall population-based incidence was 34.4 per 100,000. The incidence varied substantially with age, peaking at 82.1 per 100,000 individuals aged 75-79 but then declining coincident with a rise in mortality before day 8 in otherwise eligible patients. Extrapolating to the entire United States, for 2009 we estimated a total of 380,001 cases; 107,880 in-hospital deaths and $26 billion in hospital-related costs. CONCLUSIONS: Using a consensus-based definition, the incidence, hospital mortality and costs of chronic critical illness are substantial. Chronic critical illness is particularly common in the elderly, although in very old patients the incidence declines, in part due to an increase in early mortality among potentially eligible patients.